A study on prevalence of HIV and its associated risk factors in patients visiting tertiary care center of North India - Astha; Arti Agrawal; Ankita Soni; Neetu Chauhan; Priyanka Sahu; Sanjeev Kumar (Asian Journal of Medical Sciences, 2023)
Background: India is home to the second largest population of people living with human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) with an estimated 5.134 million infections. HIV has infected >75 million people worldwide, with an estimated 37 million people now living with the virus making it the major cause of morbidity and mortality worldwide. HIV is a significant public health problem with tremendous social and economic implications. Aims and Objectives: Our primary aim is to estimate the prevalence of HIV infection and the associated risk factors of HIV infection. Materials and Methods: This is a retrospective study of the patients who visited in integrated counseling and testing center (ICTC) and State Reference Laboratory at a tertiary care center of Agra, Uttar Pradesh from January 2017 to December 2021. The data are in accordance with NACO portal. Results: The highest HIV seropositivity was observed in 35–49 years age group in both males and females in three consecutive years 2017, 2018, and 2019, respectively. HIV seropositivity in males decreased from 8.3% in 2017 to 4.9% in 2021 and in females from 6.0% to 4.6%. The most seropositives belong to married population (41.2%) and the least in divorced population (4.2%). Overall, housewives (20.7%) were maximally affected by HIV seropositivity, followed by skilled workers (15.8%) and unemployed/retired persons (15.7%). Uneducated population had maximum seropositivity rate (35.3%). Majority of HIV positives were heterosexual non-commercial partner (47.4%), while the homosexuals were the least (1.8%) affected. Conclusion: This study highlights the most affected group of HIV seropositive population and their risk behavior. Thus, by making ICTC, more accessible to ramp up the focused screening and prevention efforts for the suspected HIV population and evolving the appropriate policies/strategies for public awareness program will help to reduce the spread of HIV infection among the masses.